Advances in Gene Therapy for Erectile Dysfunction: Promises and Challenges - Yu, Botao; Wu, Changjing; Li, Tao; Qin, Feng; Yuan, Jiuhong (Current Gene Therapy, 2018)
Erectile Dysfunction (ED) is one of the most common conditions affecting middle-aged and older men. Over the past few decades, oral phosphodiesterase type 5 inhibitors have been used to treat ED. However, these oral medications require on-demand access and are not effective in some hard-totreat populations. Moreover, there are no effective alternative treatments for ED. Based on results from preclinical models designed to provide long-term improvement of ED and other related conditions, gene therapy has shown great potential as a novel therapy for clinical management of ED. Gene therapy refers to the use of viral and non-viral vectors to deliver therapeutic genes to tissues via direct or transduced cell-mediated approaches. With the growing knowledge on the molecular mechanisms involved in the pathophysiology of ED, a number of therapeutic gene strategies have been extensively tested and proven to be effective in many animal models. However, only a few of them have been evaluated in clinical trials. This is due to safety concerns that need to be addressed before the clinical application can be considered. In this review, we summarize the key advancements in gene therapy for ED treatment, with an emphasis on the emerging stem cell-based approaches as well as other combinational strategies. The challenges facing the clinical application of gene therapy for ED treatment are also discussed.
Keywords: cell-based therapy